Development of Tablets by Direct Compression Technique: An Update - Preetha , P.; Rao, A. Srinivasa; Priyanka, Cy. (Novel Aspects on Pharmaceutical Research Vol. 7, 2023)
This chapter highlights the use of Co processed excipients in Direct Compression Tablets. Tablets constitute the most common dosage form due to economical manufacturing, accurate dosing and patient convenience. Tablets can be manufactured by direct compression or via dry, wet or melt granulation of drug(s)/excipient(s) mixture. The direct compression approach entails nothing more complicated than compressing a dry powder mixture that contains the medication and different excipients. In addition to pre-processing a single substance to create immediately compressible excipients, co-processing of two or more components can also be used to create composite particles or co-processed excipients. The direct compression process is highly influenced by powder characteristics such flowability, compressibility, and dilution potential. A greater synergy between excipient manufacturers and the pharmaceutical manufacturer in the future is going to help in the development of tailor made designer excipients complying with safety, performance, and regulatory issues.